Self-efficacy as a predictor of the individual’s future links with the employing organization - Balsan, Laércio André Gassen; Bastos, Antônio Virgílio Bittencourt; Costa, Vânia Medianeira Flores; Schleder, Marcus Vinicius Nascimento; Balsan, Fernanda Binotto Vizzotto (Revista de Administração da UFSM, 2021)
Purpose: This study analyzes the influence of the perception of self-efficacy on the commitment, entrenchment, and consent bonds that the individual will establish with the employing organization. Design/methodology/approach: This is a longitudinal panel-type survey composed of two data collections: one applied before the individual joined the organization, and the other applied nine months after joining the contracting company. Findings: The main results show the commitment established by individuals, with the contracting organization, can be predicted by the perceived self-efficacy of the individual measured before joining the organization. This suggested that the organization gives preference, at the time of hiring, to individuals with greater self-efficacy, as they will tend to develop higher commitment bond when compared to workers with lower self-efficacy. Besides the dispositional factors, other aspects arising from the individual/organization relationship will be involved in the development of the bond, and will be up to the company’s people management team to ensure adequate conditions for the building of a strong affective bond. Research limitations/implications: To better understand future linkage, other variables need to be tested to verify what are the main antecedents of the future linkage of the individual. A gap left here is the absence of data collection through interviews, which would enrich quantitative data, as well the addition of new variables not tested. Originality/value: Inserted in the efforts to predict how the new individual’s future relationship with the employing institution will be, this study relates self-efficacy to future commitment, entrenchment, and consent, something that does not exist in the literature.